Wireless physical layer security using encryption and channel pre-compensation - Tahir, Mohammad; Jarot, Sigit Puspito Wigati; Siddiqi, Muhammad Umar (2010)
In this paper we propose a scheme that provides physical layer security by combining two techniques known as encryption and channel pre-compensation. Encryption transforms the original signal constellation into a higher order constellation based on the key sequence generated by AES in counter-mode. Channel pre-compensation is performed based on the knowledge of channel, which is location specific, at the transmitter. These two techniques distort the original signal constellation which can only be recovered by the intended receiver. The proposed scheme not only makes the estimation of the constellation difficult but also the type of modulation that is used for the adversary. BER (bit error rate) is used as performance metric. We find that the adversary suffers from high BER as compared to the legitimate user; hence providing secure communication.